Methodology of training competences to solve addition and subtraction problems at high preschool age - Mihaela PAVLENCO (Acta et Commentationes, Sciences of Education, 2025)
The process of solving the addition and subtraction problems at the preschool level represents a fundamental component of early mathematical education. the methodology of training competences to solve addition and subtraction problems at high preschool age emphasizes active, child-centered learning, supported by visual aids, manipulatives, and guided questioning. the teaching approach involves a structured sequence consisting from understanding the problem, identifying known and unknown values, establishing relationships between value, and representing these relationships mathematically. furthermore, the composition of simple mathematic problems based on prior examples, stories, or visual materials encourages development creativity, critical thinking, and the ability to transfer learned concepts to new contexts. by integrating these activities into daily educational practice, children develop not only numerical concepts and arithmetic operations, but also fosters the development of logical thinking, analytical abilities, imagination and creativity, laying a solid foundation for future academic success and practical application of mathematical knowledge.